A development of chat room system prototype / Mohammad Firdaus Othman - Othman, Mohammad Firdaus (2006)
Traditionally villagers communicate with each others via face to face. However there are few constraints such as distance, weather and time limitation. Therefore the researcher proposed a development of chat room system as an alternative medium of communication with an abusive word filtering as part of the features. This project applied waterfall model. The researcher also carried out a questionnaire to 100 villagers from a different background as research's respondents. From the questionnaire researcher find out that although the selected community have the awareness of using chat as part of communication medium, but it still can be improve more to ensure community can fully utilize the application in various type of fields. This system utilized an open source application included the combination of Apache as the web server, PHP as the web base programming tools and MySQL as the database. The system allowed user to communicate online in real time. In addition, any abusive word was filtered by agent As a conclusion, the significant of the chat system is to bring together community members on the internet and decrease a digital divide among citizens. This system also can be expanded to any other web portal in order to broaden the virtual community.